2013
DOI: 10.1186/1471-244x-13-338
|View full text |Cite
|
Sign up to set email alerts
|

Cost of anxiety disorders in Japan in 2008: a prevalence-based approach

Abstract: BackgroundThe societal burden caused by anxiety disorders has likely been underestimated, while those for schizophrenia and depression have received more attention. Anxiety disorders represent a significant illness category that occurs at a high prevalence and poses a considerable burden. However, the cost of anxiety disorders in Japan has not yet been well researched. The goal of the present study was to estimate the total cost of anxiety disorders in Japan and to clarify the characteristics of this burden.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
0
19
0
3
Order By: Relevance
“…The widespread prevalence of anxiety disorders places a tremendous burden on society. Anxiety disorders cost the USA $42.3 billion in 1990, England £8.9 billion in 2007, and Japan ¥2.4 trillion ($US24 billion) in 2008 …”
mentioning
confidence: 99%
“…The widespread prevalence of anxiety disorders places a tremendous burden on society. Anxiety disorders cost the USA $42.3 billion in 1990, England £8.9 billion in 2007, and Japan ¥2.4 trillion ($US24 billion) in 2008 …”
mentioning
confidence: 99%
“…Comparing the cost of schizophrenia to other mental disorders in Japan, a report published in 201145 estimated the costs of depression and anxiety disorders in 2008 using the same methodology. This 2011 report and the result of our study reported here, when taken together indicate that for all three of these mental disorders the indirect costs accounted for the greater part of the societal cost (72% in schizophrenia; 91% in depression; and 98% in anxiety disorders).…”
Section: Discussionmentioning
confidence: 99%
“…Absenteeism and presenteeism were not included as cost components in our estimation of the cost of schizophrenia. However, considering the low employment rate and the low prevalence rate of patients with schizophrenia compared to those with depression or anxiety disorders (both approximately one third of the employment rate and prevalence rate of depression based on Sado et al),45 even if the cost of these components were estimated, it would not have had a great influence on the composition of the indirect costs. (An approximate estimate of the absenteeism and presenteeism costs in schizophrenia might be JPY 170 billion [USD 1.46 billion]; less than 10% of the unemployment cost of schizophrenia).…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, in Japan, the cost of treating anxiety disorders reached USD 20.5 billion in 2008. 38 We believe that these costs are high in Indonesia. The present study aimed to retrospectively determine the medication profile and estimate the treatment costs in from the medical records of new outpatients with schizophrenia, bipolar disorder, depression, and anxiety disorders from a healthcare perspective at one of the national referral hospitals in Indonesia from 2016 to 2018.…”
Section: Introductionmentioning
confidence: 99%